2015
DOI: 10.1016/j.cca.2014.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and the cardiorenal connection in heart failure. Circulating hormones:biomarkers or mediators

Abstract: Heart failure (HF) is a syndrome characterized by a complex pathophysiology which involves multiple organ systems, with the kidney playing a major role. HF can present with reduced ejection fraction (EF), HFrEF, or with preserved EF (HFpEF). The interplay between diverse organ systems contributing to HF is mediated by the activation of counteracting neurohormonal pathways focused to re-establishing hemodynamic homeostasis. During early stages of HF, these biochemical signals, consisting mostly of hormones and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 70 publications
(81 reference statements)
0
20
0
1
Order By: Relevance
“…Interestingly, the changes observed in WAT were not accompanied by significant changes in fibrosis or oxidative stress status as we might expect in response to HFpEF 39, 40 . Notably, neutrophil content was higher in both eWAT and iWAT.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Interestingly, the changes observed in WAT were not accompanied by significant changes in fibrosis or oxidative stress status as we might expect in response to HFpEF 39, 40 . Notably, neutrophil content was higher in both eWAT and iWAT.…”
Section: Discussionmentioning
confidence: 53%
“…Similarly, we examined natriuretic peptide receptors in adipose depots and found that the ratio of npra to nprc, was increased in eWAT of HFpEF mice indicating increased signaling and/or decreased clearance, and demonstrating that natriuretic peptides may play a role in p38 MAPK activation. Furthermore, anp and bnp expression levels, which are primarily synthetized in the heart with increased expression in HFpEF 16, 40 , were increased in the LV from mice with HFpEF. We thus propose that the natriuretic peptides secreted from the heart play an important role in the changes observed in WAT and this pathway may be a target for drug development in HFpEF.…”
Section: Discussionmentioning
confidence: 96%
“…The failing heart also induces structural and functional changes in distant organs such as the kidneys and the lungs [2,3]. Eventually, a vicious circle of pathophysiological processes is formed between these organs leading to end-stage heart failure [4,5]. In this context, circulating biomarkers that reflect the status of this multi-organ pathophysiology may be a valuable clinical tool, as these biological signals precede decompensation and may provide early organ-specific information in CHF.…”
Section: Introductionmentioning
confidence: 99%
“…The group of Prof Burnett (Buglioni and Burnett) will open the Special Issue on Biomarkers in Heart Failure with a review of the pathophysiology of heart failure and a discussion on the difference between markers and mediators of the process of HF [1]. Thereafter AnneCatherine Pouleur will give us an overview of the panel of biomarkers clinicians (should) prefer for diagnosis and management of their patients with HF with reduced ejection fraction [2].…”
mentioning
confidence: 99%